Hmm I’ve done this before but I can’t remember sorry but I will try and think
27.43 * 4.5 = 123.435
Joe jogged 123.435 meters
Answer:
15x - y = - 6.....15x + 6 = y...so we sub in 15x + 6 in for y on the other equation
5x - 3y = -13
5x - 3(15x + 6) = -13 <== the new equation
Step-by-step explanation:
Answer:
Quadratic
Step-by-step explanation:
Linear has a constant growth and exponential cannot be negative.
Answer:
(x + 5, y + 1)
Step-by-step explanation:
As we can see, what we have is a translation
let us pick a point
G( -5,-2)
To;
G’(0,-1)
so the shift on the x-axis is;
(0-(-5)) = 5
shift on the y-axis is;
(-1-(-2) = 1
we have a rightward shift of 5 units on the x-axis and 1 unit on the y-axis
So we have the rule as;
(x + 5, y + 1)